Antecedent Hospital Environment, Communication and Responsiveness in Hospitals during the Covid-19 Pandemic According to Patient Perceptions of Willingness to Recommend - Hendsun Hendsun; Hendra Achmadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Patient recommendations are the most basic form of marketing. However, hospitals often face patient reluctance to recommend them. This study uses independent variables in the form of the hospital environment, communication with patients, and responsiveness to patient needs, which are components of the HCAHPS questionnaire to measure the overall rating of the hospital as a mediating variable. The independent variable will be tested for its effect on willingness to recommend the hospital. This type of research is quantitative research with hypothesis testing (hypothesis test). This study obtained 164 respondents willing to survey from January to February 2022 and processed using PLS-SEM. The dependent variable hospital environment, communication with patients, and responsiveness to patient needs gave an R2 value of 0.675 to the overall rating of the hospital mediating variable. The mediating variable succeeded in showing a strong positive influence on willingness to recommend with R2 0.624 and mediated the independent variable's influence. The hospital environment, communication with patients, and responsiveness to patient needs have a significant positive effect on the overall rating of the hospital, which then describes a significant positive effect on willingness to recommend.